Cellular responses and gene expression profiles of colonic Lgr5+ stem cells after low-dose/low-dose-rate radiation exposure. (21st December 2017) - Otsuka, Kensuke; Suzuki, Keiji; Fujimichi, Yuki; Tomita, Masanori; Iwasaki, Toshiyasu
Abstract: We previously found that high-dose-rate radiation induced a replenishment of the colonic Lgr5 + stem cell pool, whereas low-dose-rate radiation did not. To identify key molecules that determine the dose-rate effects on this stem cell pool, we harvested colonic Lgr5 + stem cells by cell sorting at 2 weeks after exposure to 1 Gy of high-dose-rate (30 Gy/h) or low-dose-rate (0.003 Gy/h) radiation and analyzed their gene expression profiles using RNA-Seq. We found that pathways related to DNA damage response, cell growth, cell differentiation and cell death were upregulated in Lgr5 + stem cells irradiated with high dose rates, whereas pathways related to apical junctions and extracellular signaling were upregulated in low-dose-rate–irradiated colonic Lgr5 + stem cells. Interestingly, biological events involving apical junctions are known to play an important role in the exclusion of transformed cells that are surrounded by normal epithelial cells through 'cell competition'. We speculated that cell competition, through apical junctions and extracellular ligands, might contribute to the dose-rate effect on Lgr5 + cell replenishment. To understand this mechanism, we focused on 69 genes that were significantly upregulated in low-dose-rate–irradiated cells, which we named DREDGE (D ose-R ate E ffect D etermining GE nes). Based on these findings, we propose a possible mechanism underlying the dose-rate effect observed in the colonic stem cell pool.